Halal Studies: Various Approaches and Research Designs - Devid Frastiawan Amir Sup; Nur Ahid; Nadia Mira Kusumaningtyas (AL-IKTISAB: Journal of Islamic Economic Law, 2025)
Research on halal studies continues to develop and demonstrates rapid trends and significant growth, meaning it remains highly relevant today and into the future. The research approaches available are also highly diverse. The increasing complexity of human life, particularly for Muslims, necessitates new developments in approaches and methodological aspects, as it inevitably overlaps with other disciplines. This research aims to explore the variety of approaches and designs in halal studies research. This research employed qualitative methods with a literature review approach. The results indicate that halal studies research can be conducted through qualitative, quantitative, or mixed methods, using various approaches, such as monodisciplinary, intradisciplinary, crossdisciplinary, multidisciplinary, interdisciplinary, and transdisciplinary. Research design is the most important aspect in formulating the research's novelty, significance (usefulness), and contribution. These aspects include the research title, research problem, research focus, research theory, population and sample, data collection instruments and techniques, and data analysis. The importance of research design lies in its function as a foundation for ensuring valid and reliable research data, thus producing credible and accountable findings. Research design provides a systematic guide for planning, collecting, and analyzing data to accurately address research questions and provides a framework for efficient research execution and replication by other researchers.